1995
DOI: 10.1007/bf03160669
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prescribed fire on moist-soil vegetation and soil macronutrients

Abstract: Plant succession and various environmental conditions can decrease productivity of wetlands managed intensively for wildlife. Although prescribed fire frequently is used to alter plant composition and structure in semipermanent wetlands, the impacts of fire on species composition and production of seed in moist-soil impoundments have not been quantified. Therefore, I compared species composition, seed produclion, and soil macronutrient concentrations at the end of the growing season on unburned control sites (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 20 publications
2
16
1
2
Order By: Relevance
“…Playa soils have a pH lower than expected for a freshwater wetland with a mineral soil (-> 7) (Mitsch and Gosselink 1993)• Also, our pH values were slightly lower than those reported by Allen et al (1972) for other playas (6.~6.5) but similar to moist-soil impoundments in Missouri (5.4-5.5;Laubhan 1995). Therefore, generalization of pH effects on soil chemistry to playas is unwarranted, and further investigation into the influence of pH on soil-plant relationships is necessary.…”
Section: Soil Physical-chemical Variablescontrasting
confidence: 53%
“…Playa soils have a pH lower than expected for a freshwater wetland with a mineral soil (-> 7) (Mitsch and Gosselink 1993)• Also, our pH values were slightly lower than those reported by Allen et al (1972) for other playas (6.~6.5) but similar to moist-soil impoundments in Missouri (5.4-5.5;Laubhan 1995). Therefore, generalization of pH effects on soil chemistry to playas is unwarranted, and further investigation into the influence of pH on soil-plant relationships is necessary.…”
Section: Soil Physical-chemical Variablescontrasting
confidence: 53%
“…In their study on tropical soils, Ketterings and Bigham (2000) observed that the content of exchangeable cations and C and N had decreased to pre-burn levels in just a few weeks to a few months. Laubhan (1995) proved lack of differences in soil structure and macronutrients content between burnt and unburnt soils as soon as a few months after fi re. On the other hand, according to Dikici and Yilmaz (2006) the effects of fi re on particular soil properties (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Such fi res can be used as a management tool for the removal of shrubs, enhancement of biodiversity or for protection of rare plant species (Middleton et al 2006, Kimura andTsuyuzaki 2011). Surface fi res have usually short-term, minor infl uence on the soil chemical features, especially in comparison to smoldering fi res (Laubhan 1995, Smith et al 2001, which can last up to a few months and result in burning out of the muck surface layer of peat deposit (Kania et al 2006, Watts andKobziar 2013). The temperatures recorded during a smoldering fi re are lower than during a typical fl ame combustion and range from 300 to 600°C.…”
Section: Introductionmentioning
confidence: 99%
“…These methods are used to reduce dense stands of vegetation to create hemi-marsh conditions, to promote plant species that provide seeds eaten by waterfowl, and to remobilize nutrients held in dead standing vegetation (Ward 1968, Hackney and de la Cruz 1981, Diiro 1982, Herndon et al 1991, Laubhan 1995. Burning can destroy dormant mosquito eggs in dry wetland sediments (Wallace et al 1990, Whittle et al 1993, and mosquito densities in wetlands are lower in areas where emergent plants were burned or mowed than in unmanipulated areas Resh 1992a, de Szalay et al 1995).…”
Section: Introductionmentioning
confidence: 99%